Destination image as a determinant of tourist satisfaction and loyalty - Guliling, Hasnawati; Abdul Aziz, Yuhanis; Bojei, Jamil (Universiti Teknologi MARA Cawangan Sabah, 2016)
Rapid development in the tourism industry has created new challenges for tourism marketers. In the climate of growing competition, one of the major tasks for destination marketing specialists lies within the area of building an effective destination positioning strategy and the core element of this positioning mechanism is creating a positive image of the destination. Therefore, an understanding of what constitutes destination image that leads to tourist satisfaction and loyalty can help the nation to formulate marketing strategies and better position itself as a competitive destination. The purpose of this paper is to conceptualise the underlying dimensions of destination image that can influence tourist satisfaction and loyalty. Theoretically, this paper contributes to the body of knowledge by emphasising key antecedents affecting tourist behaviour. Practically, the research findings are of suggestive value to image building and destination planning for Malaysian tourist destinations.